Personality of Children and Classroom Bullying: The Role of Parental Physical and Psychological Aggressio - Syed Afzal Shah (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2019)
Objectives: To explore the impact of parental aggression (physical and psychological) on  classroom bullying and to explore the effect of parental aggression on personality traits viz. neuroticism, extraver-   sion, and agreeableness factors of personality of secondary school students.